A Contrastive Analysis of Chinese and Indonesian Nominal Sentences - Ayu Trihardini (Lingua Cultura, 2022)
The comparative study aimed to describe the characteristics of Chinese and Indonesian nominal sentences. The research contributed to teaching Chinese as a second language and the field of translation as well. Chinese was being studied all over the world, and Indonesia was no exception. Nevertheless, contrastive analysis between Chinese and Indonesian in the field of syntax were still limited. Nominal sentences are one of the classifications of sentences based on the predicate form. Accordingly, Chinese and Indonesian nominal sentences have similar definitions but differed in the words or phrases that form the predicate. The data in the contrastive analysis study were Chinese and Indonesian nominal sentences from short stories, novels, other literary works, and examples of related grammatical works. The data were analyzed using the James procedure and the contrastive analysis method with four steps described by Di Pietro. The finding of the contrastive analysis indicates that in both languages, nominal sentence usage is limited under certain conditions; some Chinese nominal sentences will become verb sentences when translated into Indonesian. Also, Chinese and Indonesian nominal sentences differ in their negative forms. The error analysis indicates that Indonesian students still lack knowledge of Chinese nominal sentences and characteristics.